THE ROLE OF ISLAMIC THEOLOGY TEACHERS IN BUILDING CLASS CLIMATE IN STUDENTS SIKKA FLORES REGENCY, EAST NUSA TENGGARA - Syahrul Syahrul; Salahuddin Salahuddin; Muh. Rapi (Universitas Islam Negeri Alauddin Makassar, 2021)
This article discusses the role of Theology Teachers in Building a Classroom Climate for Students at Mts Nur Muhammad Pemana, Sikka Flores Regency, NTT. This article uses a qualitative research methodology with a focus on research (Field Research) in obtaining documents related to this issue and using multiple sites. Teachers have a very big role in creating a conducive classroom climate, so teacher competence is needed. A good classroom climate will describe demonstrations, where the teacher's behavior is more active in creating a conducive classroom climate. where a teacher provides opportunities for optimal learning achievement. Students who live in a pleasant classroom atmosphere are expected to be able to produce better performance when compared to children who live in an unpleasant classroom atmosphere. The author has come to the conclusion that the role of the moral theology teacher of class VIII MTs Nur Muhammad starting from the role of class management is both from students and the state of the classroom environment before the lesson begins, then after that hold a little dialogue or story with the aim of conditioning students to learn.